The Meaning and Functions of a Literary Text as a Factor in the Development of the Aesthetic Culture of the Future Teacher of Primary Education - Sobirjanovna, Dustova Dildora; Aziza, Mahmudova (European Journal of Life Safety and Stability (2660-9630), 2021)
This article reveals the meaning and functions of a literary text as an effective means of forming the aesthetic culture of primary education students in the process of teaching the Russian language. On the example of using one art test in the classroom, the factors for the development of the aesthetic culture of future teachers are formulated.